(untitled) (Communications in Computational Physics, 2006)
Computational simulation of the radiating structure of a microwave from a pyramidal horn has been successfully accomplished. This simulation capability is developed for plasma diagnostics based on a combination of three-dimensional Maxwell equations in the time domain and the generalized Ohm's law. The transverse electrical electromagnetic wave of the TE1,0 mode propagating through a plasma medium and transmitting from antenna is simulated by solving these governing equations. Numerical results were obtained for a range of plasma transport properties including electrical conductivity, permittivity, and plasma frequency. As a guided microwave passing through plasma of finite thickness, the reflections at the media interfaces exhibit substantial distortion of the electromagnetic field within the thin sheet. In radiating simulation, the edge diffraction at the antenna aperture is consistently captured by numerical solutions and reveals significant perturbation to the emitting microwave. The numerical solution reaffirms the observation that the depth of the plasma is a critical parameter for diagnostics measurement.